Diseño de un brazo robótico para utilizar en un laboratorio de automatización (2019)
This project has been developed in order to develop a robotic arm. Our main work has been carried out. In the automation laboratory of the University of America. As a second application, through the use of the prototype, students of Mechanical Engineering applied knowledge in areas such as electronics, automation, instrumentation and process control, as well as giving an overview of how these devices are used. implemented. Currently in all industries around the world, including in Colombia.